Effects of beta-alanine supplementation on recovery and performance factors in male soccer players - Hamzekolaee, A. M.; Safarzade, A.; Esmaeeli, A. (Asian Journal of Sports Medicine, 2023)
Background: There is growing interest in using dietary supplements to delay fatigue, accelerate recovery time, and improve the performance of athletes. Objectives: In the present study, we investigated the effect of beta-alanine supplementation on the levels of some metabolic indexes related to recovery and the performance of soccer players. Methods: Sixteen young soccer players [age: 20 ± 1.19 years, weight: 67.67 ± 8.9 kg, height: 176.38 ± 5.54 cm and body mass index (BMI): 21.76 ± 2.12 kg/m2] completed this study. The subjects were randomly assigned into two groups. They were supplemented with 5g/day beta-alanine (BA) (BG, N = 8) or placebo (PG; N = 8; maltodextrin) for three weeks. Maximum oxygen consumption, explosive power, and recovery-related blood parameters (creatine kinase, lactate dehydrogenase, urea) were measured in two stages before and after supplementation. Results: No significant change was observed in the serum creatine kinase level after the intervention (P = 0.061). Also, no significant difference was observed in serum levels of other blood factors, such as lactate dehydrogenase (P = 0.061) and urea (P = 0.061). Regarding performance factors, no significant changes were observed in aerobic power (P = 0.061) and explosive power (P = 0.061). Conclusions: Our results suggest that beta-alanine has no effect on reducing metabolic factors related to recovery and may improve the aerobic power of soccer players.